Real Income and Wealth of the Elderly - Hurd, Michael D.; Shoven, John B. (American Economic Review, 1982)
The recent White House Conference on Aging graphically demonstrated public concern over the welfare of the growing elderly segment of the U.S. population. How is this group faring economically? Have they suffered from the stagflation of the last decade, or have they been sheltered from economic harm by a combination of government programs and fortuitous asset holdings? How vulnerable were they as a group to the inflation of the 1970's? We answer some of these questions by focusing on the economic welfare of the elderly over the last decade. We assess the level and composition of real income and wealth of the elderly; we compare their incomes to those of the general population; and we compute a measure of their vulnerability to unexpected increases in the price level. We note, however, that there are many other important indicators of the welfare of the elderly, such as the increasing life expectancy, changing living arrangements and housing, trends towards earlier retirement, and decreasing intergenerational contact. We do not consider these issues, so our results do not give a complete assessment of the welfare of the elderly. We believe our results provide a good assessment of how their economic position changed over the decade.